2020
DOI: 10.1177/1729881420968702
|View full text |Cite
|
Sign up to set email alerts
|

A long short-term memory neural network model for knee joint acceleration estimation using mechanomyography signals

Abstract: With the growth of the number of elderly and disabled with motor dysfunction, the demand for assisted exercise is increasing. Wearable power assistance robots are developed to provide athletic ability of limbs for the elderly or the disabled who have weakened limbs to better self-care ability. Existing wearable power-assisted robots generally use surface electromyography (sEMG) to obtain effective human motion intentions. Due to the characteristics of sEMG signals, it is limited in many applications. To solve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Although previous studies have confirmed that end-to-end deep learning models can extract representative features from sEMG signals [40][41][42], after all, deep learning models are like a black box with poor interpretability. In our experiment, we therefore first manually selected a large number of features, filtered them through EFS, and then fed them into a deep learning model for training.…”
Section: Discussionmentioning
confidence: 93%
“…Although previous studies have confirmed that end-to-end deep learning models can extract representative features from sEMG signals [40][41][42], after all, deep learning models are like a black box with poor interpretability. In our experiment, we therefore first manually selected a large number of features, filtered them through EFS, and then fed them into a deep learning model for training.…”
Section: Discussionmentioning
confidence: 93%
“…Over the past decades, a lot of work has been performed by many experts using muscle activity to predict joint angle [3], acceleration [4], torque [5], muscle force [6][7][8][9], fatigue effect [10], etc. In particular, estimating muscle force from muscle activity in these investigations is a challenging task, which has many potential applications such as diagnosis of muscle dysfunction, rehabilitation training, prosthetic assistive devices, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, MMG can also provide important information on muscle activity and motor unit recruitment patterns [16], which can be detected on the skin surface above the target muscle by accelerometers, piezoelectric microphones, etc. [1,4,13,17]. Even though MMG is influenced by many factors such as muscle morphology and the physical environment [18], it has significant advantages over sEMG with no skin preparation, negligible skin impedance, no need for precise test positioning, and less electronic noise interference [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [14], a generalized three domains fuzzy wavelet neural network (TDFWNN) algorithm was used to accurately estimate the force from an EMG signal without prior knowledge of the biomechanical model. In [15], taking the quadriceps femoris muscle as an example, the acceleration of the knee joint was estimated by using the long short-term memory (LSTM) neural network model. In [16], the Fuzzy Theory and Deep Learning model based on EMG signals was proposed to estimate the applied forces in robotic surgery.…”
Section: Introductionmentioning
confidence: 99%